Gombrowicz od tyłu Projekt krytyki analnej na przykładzie powieści Ferdydurke - Kaliściak, Tomasz (Śląskie Studia Polonistyczne, 2016)
The article proposes an “anal” reading of Witold Gombrowicz’s Ferdydurke from the perspective of the so‑called “anal turn” in the research on masculinities within the field of queer theories. The author presents an overview of theoretical perspectives, in which anality has been recognized as a suppressed component of male identity (e.g. Freud, Bataille, Kristeva, Deleuze and Guattari, Hocquenghem, Laporte). Masculinity seen from this angle is based on a radical shift of the foundation from a phallogocentric position to a more dispersed, non‑centralist, and thus more difficult to grasp, “anal” approach. In Gombrowicz’s work this change is best illustrated in the reflections on the subject of privacy. The subjectivity of the main character of Ferdydurke organises himself not around phallus but anus, and this new, radically shifted and dispersed subjectivity is called by Gombrowicz the private (or “upupiona”, “pampered”) masculinity, which reactivates the suppressed anality. The author analyses Ferdydurke also in the context of a peculiarly understood theory of “anal work,” in the light of which a literary work appears as an excrement and writing as excretion.